Factors Affecting Work Fatigue in Workers of Process Plan Department Area at PT Citra Palu Minerals - Lusia Salmawati; Muhammad Zikra; Arwan; Muhammad Sabri Syahrir (Tadulako Social Science and Humaniora Journal, 2024)
Work fatigue is a condition that causes a decrease in a person's efficiency and performance, so it can increase the occurrence of work accidents, and harm themselves and their companies, due to decreased productivity. The purpose of this study was to examine the effect of length of service, nutritional status, and workload on work fatigue in the processing planning department area at PT Citra Palu Minerals. This study uses quantitative research with a Cross-Sectional approach. The sampling technique in this study was determined by incidental sampling with a total sample of 54 respondents. Data collection using questionnaires, measuring instruments finger pulse oximeter, and body mass index calculation. Data analysis used is univariate, bivariate, and multivariate analysis. The results showed workload p value = 0.006 means it has a relationship with fatigue, nutritional status p value = 1,000 and tenure has p value = 0.188 means it does not have a significant relationship to fatigue in workers. The most influential factor on fatigue is workload with an Exp (B) value = 7.500.